Pelaksanaan Asas Praduga Tak Bersalah sebagai Upaya Perlindungan Hukum bagi Tersangka Selama Penyidikan - Maulana Ramadhan; Ade Saputra; Egghy Seliyan Putra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The presumption of innocence is a fundamental principle in criminal procedural law, which affirms that every individual suspected, arrested, detained, or charged must be presumed innocent until a final and binding court decision is issued. This research is based on the fact that the application of this principle is still frequently violated in investigative practice, including through acts of violence by law enforcement officers, hasty determination of suspect status, and media reporting that shapes public opinion as if the suspect is guilty. The legal issues examined in this research focus on the extent to which the application of the presumption of innocence affects the protection of suspects' rights during the investigative process, and how it is implemented in law enforcement practice in Indonesia. Based on this, this research formulates three main issues: (1) what is the concept and legal basis of the presumption of innocence in the Indonesian criminal procedural law system; (2) how does the application of this principle affect the protection of suspects' rights during the investigative process; and (3) what factors hinder its implementation in practice. The research method used is a normative juridical method with a statutory, conceptual, and case-based approach.